Exploring weak intermolecular interactions in thiocyanate-bonded Zn(II) and Cd(II) complexes with methylimidazole: crystal structures, Hirshfeld surface analysis and luminescence properties - Di Santo, Alejandro (2018)
Four new thiocyanate-Zn(II) and -Cd(II) complexes with 1-methylimidazole (1-MeIm) and 2-methylimidazole (2-MeIm), namely, Zn(1-MeIm)2(SCN)2 (1), Zn(2-MeIm)2(SCN)2 (2), Cd(1-MeIm)4(SCN)2 (3) and polymeric [Cd(2-MeIm)2(SCN)2]n (4), have been synthesized and characterized by IR, Raman and UV-Vis spectroscopy. The thermal behavior for all complexes was evaluated by thermo-gravimetric analysis and differential thermal analysis. The crystal structures of complexes 1–4 were solved by single-crystal X-ray diffraction methods. A study of intermolecular interactions in the solid state compounds revealed that molecules are linked by weak N–H⋯S and C–H⋯S hydrogen bonds and also by C–H⋯π interaction in the case of structures 2–4, which are responsible for the formation and stability of the molecular assemblies. Hirshfeld surfaces and 2D-fingerprint plots allowed us to visualize the intermolecular contacts and their relative contributions to the total surface for each compound. A comparative analysis against similar halogen-bonded complexes was carried out to investigate the tendency of inter-molecular interactions to form contacts in crystals by using the enrichment ratio descriptor. The emission spectra of the free imidazole derivatives and their Zn(II) and Cd(II) complexes were recorded in acetonitrile solutions. The emissions observed in the spectra of complexes were ascribed to the intra-ligand transitions and ligand-to-metal charge transfer and we have observed an interesting correlation between the fluorescence intensities and C–H⋯π interactions.